Implementation of Mobile-Based ZIS (Zakat, Infaq, Shadaqah) Management Information System - Reni Widyastuti; Tri Hartati; Budi Supriyadi (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2023)
LAZIS Babussalam is a social institution that provides services for receiving and distributing zakat, infaq and alms (ZIS) funds based on mosque congregations and the community who live in the Cipinang area, East Jakarta. Currently, the muzakki / donor data management system is only done manually and donors must come directly to the institutional admin. Management of transaction data and muzakki data is recorded and collected from receipts every time a transaction process occurs, then a monthly recapitulation is carried out in an Excel document. This makes data processing take quite a long time and is prone to errors in recording and data loss can also occur when making reports so that it can reduce muzakki's trust. The author designed an Android-based information system which is a solution to overcome problems, especially in the ZIS acceptance system. In this study, the authors used the system development method, namely Waterfall where the tool in system development is the unified modeling language (UML). The implementation of the ZIS management information system can be carried out properly which makes it easier for institutions and muzakki to quickly and easily find and receive valid reports of funds and their distribution